Legal Analysis of the Implementation of Maritime Crimes Based on Law Number 17 of 2008 Concerning Maritime Affairs - Junaedi, Junaedi; Ali, Muhammad (SALAM: Jurnal Sosial dan Budaya Syar-i, 2024)
Law is a series of regulations and norms that govern society to create order and justice in national life. However, not all individuals are willing to comply with applicable legal regulations; therefore, effective law enforcement is necessary to ensure compliance with these regulations. In the context of shipping, law plays a crucial role in maintaining the security, safety, and protection of the maritime environment, as stipulated in Law Number 17 of 2008 concerning Shipping. Violations in the field of shipping, such as operating ships without meeting safety standards, compromising security, and failing to protect the maritime environment, can threaten human safety, environmental sustainability, and naval security stability.This study aims to analyse the application of law to perpetrators of shipping crimes based on Law Number 17 of 2008 concerning Shipping, and to identify factors that influence the occurrence of violations in ship operations. The research method used is a normative juridical approach, which focuses on the study of the application of positive legal norms in enforcing criminal law in the shipping sector.The results of the study indicate that law enforcement against maritime crimes has not been optimal due to several factors, including low legal awareness, weak supervision and enforcement, and economic interests that often prioritize financial gain over safety and environmental protection. Increased legal awareness, stricter supervision, and firm law enforcement are necessary to ensure that perpetrators of maritime crimes are subject to effective legal sanctions, thereby providing a deterrent effect.Keywords: Crime, Shipping, Perpetrators.